The IDO1-induced kynurenines play a major role in the antimicrobial effect of human myeloid cells against Listeria monocytogenes. Issue 4 (May 2014) - Niño-Castro, Andrea; Abdullah, Zeinab; Popov, Alexey; Thabet, Yasser; Beyer, Marc; Knolle, Percy; Domann, Eugen; Chakraborty, Trinad; Schmidt, Susanne V; Schultze, Joachim L
Induction of indoleamine 2, 3-dioxygenase (IDO1) is an established cellular response to infection with numerous pathogens. Several mechanisms, such as IDO1-mediated tryptophan (Trp) depletion, but also accumulation of Trp catabolites, have been associated with the antimicrobial effects of IDO + cells. Recent findings of IDO1 as an immunoinhibitory and signaling molecule extended these previous observations. Using infection of professional phagocytes with Listeria monocytogenes ( L.m. ) as a model, we illustrate that IDO1 induction is a species-specific event observed in human, but not murine myeloid, cells. Knockdown and inhibition experiments indicate that IDO1 enzymatic activity is required for the anti- L.m . effect. Surprisingly, the IDO1-mediated antimicrobial effect is less prominent when Trp is depleted, but can be significantly amplified by tryptophan excess, leading to increased accumulation of catabolites that promote enhanced bactericidal activity. We observed a pathogen-specific pattern with kynurenine and 3-hydroxy-kynurenine being most potent against L.m., but not against other bacteria. Hence, apparent discrepant findings concerning IDO1-mediated antimicrobial mechanisms can be reconciled by a model of species and pathogen-specificity of IDO1 function. Our findings highlight the necessity to consider species- and pathogen-specific aspects of host–pathogen interactions when elucidating the individual role of antimicrobial proteins such as IDO1.